Protection of Maritime Law on Fishery Zone at the Coast Border of West Sumatera - Magdariza; Najmi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2022)
In the few months there is a high intensity of illegal fishing at Indonesian waters. The most potential area located in the coast border of West Sumatera facing the high seas and Indian Ocean that have long been a target from abroad fishing boats. Geographically, there are three areas located in strategic west coast of Sumatera such as Padang City, South Coast District, and Mentawai District. By the situation of opened-coast territorial geography, it is susceptible for illegal fishing of tuna by the local or abroad ships. The observed problems in this research are finding causing factors of illegal fishing in west coast of Sumatera to protect the waters environment under the local wisdom, how to implement the countermeasures of illegal fishing in the west coast of Sumatera. Moreover, there is a special attempt to find out the system and proper policy to cope with the potential happening often of illegal fishing that threatens the waters protection in west coast of Sumatera. The dominant method used in research is qualitative approach by implement two legal studies such as socio legal and normative legal study used in research on doctrines or useful principles of law. Moreover, characteristically this research categorized as the analytical descriptive.